Fearless Leadership: Examining the Influence of Courage in Military Command - Sarjito, Aris (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2024)
Abstract This study investigates courage in military leadership, its impact on decision-making, inspirational influence, and the evolution of military institutions under courageous leaders in real-world scenarios and historical adversity. Using secondary data sources, including historical accounts and documented military actions, the research identifies attributes and skills associated with courageous military leadership, contributing valuable insights for training programs. The findings reveal nuanced expressions of courage among military leaders, shedding light on their decision-making processes during critical moments. The study underscores the inspirational impact of courageous leadership on unit morale and cohesion, emphasizing its role in shaping the trajectory of military institutions over time. The identified attributes and skills of courageous military leadership serve as a foundation for developing effective training programs to cultivate future leaders. Keywords: courage; decision-making; fearless leadership; military command